2009
DOI: 10.1017/s0033291709991425
|View full text |Cite
|
Sign up to set email alerts
|

Genetic modelling of childhood social development and personality in twins and siblings with schizophrenia

Abstract: Abnormalities of social adjustment and personality are present in children and adolescents who later develop schizophrenia, reflecting the influence of common genetic risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 90 publications
0
15
0
Order By: Relevance
“…Crucially, the risk for Sz is increased in those with a lower IQ score, in particular in the presence of impaired nonverbal reasoning (49). Furthermore, recent work has shown that there are significant common genetic influences acting on the covariance between IQ, schizotypy, abnormal social functioning, and schizophrenia (50). This suggests that the same genetic factors that impair intelligence, increase schizotypy, impede social development, and decrease BV in childhood also determine the liability to Sz (39,50).…”
Section: Discussionmentioning
confidence: 99%
“…Crucially, the risk for Sz is increased in those with a lower IQ score, in particular in the presence of impaired nonverbal reasoning (49). Furthermore, recent work has shown that there are significant common genetic influences acting on the covariance between IQ, schizotypy, abnormal social functioning, and schizophrenia (50). This suggests that the same genetic factors that impair intelligence, increase schizotypy, impede social development, and decrease BV in childhood also determine the liability to Sz (39,50).…”
Section: Discussionmentioning
confidence: 99%
“…Premorbid dysfunction is strongly associated with postonset illness characteristics including severity of negative symptoms, cognitive deficits, motor slowing, and treatment refraction (e.g., Addington, van Mastrigt, & Addington, 2003; Haim, Rabinowitz, & Bromet, 2006; Larsen, McGlashan, Johannessen, & Vibe-Hansen, 1996; Levitt, O'Donnell, McCarley, Nestor, & Shenton, 1996; Silverstein, Mavrolefteros, & Turnbull, 2003). Furthermore, a history of poor functioning in childhood and adolescence in nonpsychotic adult relatives of schizophrenia patients (Shapiro et al, 2009; Walshe et al, 2007), including monozygotic twins (Picchioni et al, 2010), suggests a genetic component to this association.…”
mentioning
confidence: 99%
“…Group effects were analyzed using a regression model with standard errors that are robust against familial correlations (Binder, 1983, Picchioni et al, 2010). Regression and logistic regression with the Huber–White sandwich standard error were used to compare demographic, clinical, and behavioral variables while taking account of family clusters.…”
Section: Methodsmentioning
confidence: 99%
“…Regression and logistic regression with the Huber–White sandwich standard error were used to compare demographic, clinical, and behavioral variables while taking account of family clusters. We carried out overall group comparisons followed by post-hoc pair-wise comparisons where the initial test was significant using established testing models (Picchioni et al, 2006, Picchioni et al, 2010) in STATA 10.1.…”
Section: Methodsmentioning
confidence: 99%